Seafloor photo‐geology and sonar terrain modeling at the 9°N overlapping spreading center, East Pacific Rise. (20th December 2013) - Klein, Emily M.; White, Scott M.; Nunnery, James Andrew; Mason‐Stack, Jessica L.; Wanless, V. Dorsey; Perfit, Michael R.; Waters, Christopher L.; Sims, Kenneth W. W.; Fornari, Daniel J.; Zaino, Anne J.; Ridley, W. Ian
<x xml:space="preserve">Abstract</x> [1] A fundamental goal in the study of mid‐ocean ridges is to understand the relationship between the distribution of melt at depth and seafloor features. Building on geophysical information on subsurface melt at the 9°N overlapping spreading center on the East Pacific Rise, we use terrain modeling (DSL‐120A side scan and bathymetry), photo‐geology (Jason II and WHOI TowCam), and geochemical data to explore this relationship. Terrain modeling identified four distinct geomorphic provinces with common seafloor characteristics that correspond well to changes in subsurface melt distribution. Visual observations were used to interpret terrain modeling results and to establish a relative seafloor age scale, calibrated with radiometric age dates, to identify areas of recent volcanism. On the east limb, recent eruptions in the north are localized over the margins of the 4 km wide asymmetric melt sill, forming a prominent off‐axis pillow ridge. Along the southern east limb, recent eruptions occur along a neovolcanic ridge that hugs the overlap basin and lies several kilometers west of the plunging melt sill. Our results suggest that long‐term southward migration of the east limb occurs through a series of diking events with a net southward propagation direction. Examining sites of recent eruptions in the context of geophysical data on melt distribution in the crust and upper mantle suggests melt may follow complex paths from depth to the surface. Overall, our findings emphasize the value of integrating information obtained from photo‐geology, terrain modeling, lava geochemistry and petrography, and geophysics to constrain the nature of melt delivery at mid‐ocean ridges.